Pan-Cancer Analysis Identified Homologous Recombination Factor With OB-Fold (HROB) as a Potential Biomarker for Various Tumor Types - Liu, Xianming; Wang, Cunchuan (Frontiers in Genetics, 2022)
Background: By recruiting the MCM8-MCM9 helicase to DNA damage site, the Homologous Recombination Factor With OB-Fold (HROB) is involved in the repair of inter-strand crosslink and homologous recombination. Previous studies have shown HROB may play an oncogenic role by promoting cell proliferation and chemoresistance in several tumor types. However, the potential diagnostic and prognostic value of HROB has not been systemically explored in pan-cancer. Methods: We analyzed the expression pattern of HROB among tumor tissues and normal tissues in several public databases, including Human Protein Atlas, the Cancer Genome Atlas (TCGA) and investigated the association between HROB expression and pathological stage and patient prognosis. We also analyzed the association between HROB expression and cancer stemness and immune infiltration of Cancer-associated Fibroblasts (CAFs) and CD8+ T cells in pan-cancer. Finally, we explored the potential biological function of HROB through pathway enrichment analysis. Results: In most tumor types, HROB is overexpressed in tumor tissues compared with non-tumor tissues. High HROB expression was correlated with poor prognosis and advanced pathological stages. HROB expression was robustly correlated with cancer stemness. Moreover, significant correlations between CAFs, CD8+ T cells infiltration and HROB expression were observed in several tumor types. Pathway enrichment analysis revealed that cell cycle and mitotic regulated pathways were strongly enriched in HROB co-expressed genes. Conclusion: HROB may be a potential diagnostic and prognostic biomarker in pan-cancer which may play a role in tumorigenesis and disease progression by affecting cancer stemness of tumor tissues and immune cells infiltration.